A STUDY TO INVESTIGATE THE PERCEPTION REGARDING VACCINATION: EDUCATED AND UNEDUCATED PARENTS OF RURAL AND URBAN FAMILIES OF DISTRICT FAISALABAD - Nasir, Naina; Abbas Athar, Asad; Kousar, Rehana; Hasan, Gulfam; Ali, Rafaqat; Norin, Mehtab; Saeed, Khadeeja (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Vaccine development is one of the most remarkable scientific breakthroughs in human history and has permanently revolutionized the field of medicine and health. Since its development in the early 20th century, vaccination has significantly reduced the burden of infectious diseases, and associated morbidity and mortality and improved average life expectancy. The currents study was conducted in District Faisalabad. The current study was descriptive in nature. There were 8 towns in District Faisalabad. Out of there 8 towns, one rural town (Habib town) and one urban town (Amin town) were selected conveniently. Regarding the list obtained from the vaccinator of the related towns there were 250 households in Habib town and 180 in Amin town which were as the population of the present study. Sample size of 130 households had been drawn using website www.surveysystem.com by keeping confidence level 95% and confidence interval 7%. From each town 65 households were selected using simple random sampling technique thus making a sample size of 130 households. The collected data were analyzed by using Statistical Package of Social Sciences (SPSS). Large majority (61.5 %) of the respondents were from Rural areas. More than one third (36.9 %) of the respondents were between 36 to 40 years. More than one fifth (28.5 %) of the respondent’s education was Primary. Children should be vaccinated against diseases in general is rank ordered on 1st position with mean value 4.15. At the 2nd ranked number respondents said about vaccinations are effective for your children immune system and over all immunity with mean value 4.14. Lack of parent’s awareness regarding the vaccine’s efficacy for children is rank ordered on 1st position with mean value 4.05. At the 2nd ranked number respondents said about Parents Concerns about the vaccine’s safety/side effects with mean value 4.01. It was concluded that parents whose children were under the age of 3 had higher levels of vaccine literacy and were more likely to trust domestically produced vaccines than parents with children between the age 4 and 6. A possible reason for this might be their rather frequent contact with pediatricians or health workers due to the children’s vaccination schedule at that age. Health professionals might be helpful sources for parents to identify correct information and to correct misbeliefs on vaccines. It was suggested that the potential of community-based should interventions to improve immunization coverage in hard-to-reach areas. The study recommended that improving vaccine education and communication to address these concerns and improve vaccine uptake.